Successful Endovascular Removal of a Perforated Inferior Vena Cava Filter Complicated by a Large Retroperitoneal Hematoma: Pitfall of Catheter-Directed Thrombolysis - Ishigami, Norio; Nagai, Tomoo; Arakawa, Junko; Hisadome, Hideki; Tabata, Hirotsugu (International Journal of Angiology, 2016)
Symptomatic caval perforation is rare complication after inferior vena cava (IVC) filter insertion. A 44-year-old woman developed back pain after the placement of retrieval IVC filter during catheter-directed thrombolysis (CDT). Her computed tomography showed a large right-sided retroperitoneal hematoma. After 2 weeks, endovascular removal of the perforated filter was successfully performed without complication. Because thrombolytic agents can accelerate bleeding caused by endovascular procedures, the bleeding rate of the IVC filter deployment during CDT might be higher than expected.
Keywords: deep vein thrombosis; IVC filter complications; IVC wall penetration; thrombolysis; endovascular procedure